Implications of The Effect Of Profitability and Liquidity on Capital Structure in Mining Companies in Indonesia With Firm Size as Moderation - Arienda Gitty Ramadani; Hesniati Hesniati; Destiana Safitri (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2025)
Background – Economic growth in Indonesia in 2022 reached 5.31%, which is the highest achievement from 2014. Although Indonesia was hit by the negative impact of the Covid-19 pandemic, the economy in Indonesia continues to show resilience and increasing rapidly. The ideal capital structure is a blend of debt and equity that maximizes firm value through prudent investment choices and enhances the financial and operational performance of the business. Aim – This research is to determine the impact of internal factors on capital structure. By investigating the moderating effect of business size on the link between profitability and liquidity on capital structure, this study adds to the body of previous work. Design / methodology / approach – This study employed a quantitative research design, which entails gathering quantifiable numerical data and applying statistical analysis to determine and elucidate the relationship between variables. The study employed secondary data, which was sourced from a company’s financial documents. Purposive sampling is used in the study to choose profitable companies. This approach is being employed since the data used in the study are secondary data, which offer more comprehensive and varied data information. Eviews was used to help with the data analysis strategy used in this investigation. Findings – The hypothesis for the first hypothesis is profitability accepted to have a positive and significant effect on capital structure. Second hypothesis is accepted, and fourth hypothesis is accepted. While the third hypothesis is rejected. Research implication – According to the research, a 1% improvement in profitability (ROA) can result in a 0.06% reduction in the company's debt, raising earnings and lowering the amount of debt in the capital structure. High liquidity companies typically use their internal profits instead of taking on debt or issuing additional shares. The study's findings imply that firm size may have an impact on the relationship between capital structure and liquidity because larger, more liquid corporations are thought to be more able to pay back their loans. Limitations – The study acknowledged numerous limitations, including the use of USD exchange rates, which rendered some data meaningless, and the elimination of enterprises with unfavorable financial reports. Just 46 of the 63 profitable mining businesses listed on the IDX were examined in this study. Consequently, the study suggests that more research be done over a longer time period on various organizations or sectors. It also recommends that future research include more independent factors or mediating variables.